ANALISIS PENGHINDARAN PAJAK YANG DIPENGARUHI TINGKAT PROFITABILITAS (Jurnal Akuntansi, 2020)
This research is conducted to determine the influence of Profitability on Tax Avoidance in Coal Mining Companies Listed on The Indonesia Stock Exchange Period 2013-2017. The problem in the coal mining company is the existence of companies that have increased profitability but were followed by increased tax avoidance. The research method used is descriptive and verification analysis with a quantitative approach. The population in this study is 24 Coal Mining Companies Listed on The Indonesia Stock Exchange Period 2013-2017. Samples of research were taken using the purposive sampling method to obtain 14 coal mining companies with 70 financial statements in the period of 2013-2017. The analysis method used is multiple linear regression analysis. The result of this study showed that the profitability variables measured using Return on Asset (ROA) has negative and significant effect on Tax Avoidance which measured using Effective Tax Rate (ETR).